The correlation of Helicobacter Pylori with the development of cholelithiasis and cholecystitis: the results of a prospective clinical study in Saudi Arabia - Guraya, S Y; Ahmad, A A; El-Ageery, S M; Hemeg, H A; Ozbak, H A; Yousef, K; Abdel-Aziz, N A (European review for medical and pharmacological sciences, 2015)
Gallstone disease is a common surgical ailment. Helicobacter pylori has a role in upper gastrointestinal disorders, including gallstones. This study aimed to determine the association of H. pylori with gallstones, so developing a preventative strategy for gallstone formations. A prospective study was conducted on 95 patients referred to the surgical clinic of Al-Meeqat General Hospital, Al-Madinah Al-Munawarah, with gallstone disease. Detection of H. pylori antibodies (IgG) in serum was done in all the patients who underwent cholecystectomy. H. pylori stool antigen (HPSA) using stool samples was done for IgG sero-positive patients prior to the cholecystectomy. The bile collected from the gall bladder during operation was examined for the presence of H. pylori by Gram stain, culture and HPSA assay. Gallbladder mucosa was examined for urease A gene by polymerase chain reaction (PCR) in patients proven to be positive for stool or bile serology. Of the 95 patients, 75 (79%) were positive for H. pylori antibodies. Twenty-six (34.7%) patients were positive with H. pylori antigens in bile and 21 (28%) with H. pylori antigens in the stool samples. Among these 47 patients, PCR was positive in 29 (62%) subjects. H. pylori couldn't be detected among the studied patients by using either Gram stain or culture. The presence of H. pylori in bile may indicate a significant risk for cholelithiasis. PCR is a rapid reliable method for the detection of H. pylori DNA in bile. This rapid molecular approach together with culture and immunological methods could help clinicians to effectively manage patients at high risk of developing gallstones at an earlier stage.